2016
DOI: 10.1007/s10329-016-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Food begging and sharing in wild bonobos (Pan paniscus): assessing relationship quality?

Abstract: Food transfers are often hypothesised to have played a role in the evolution of cooperation amongst humans. However, they also occur in non-human primates, though no consensus exists regarding their function(s). We document patterns of begging for food and success rates as well as associated factors that may influence them for wild bonobos at LuiKotale, Democratic Republic of Congo. Our data, collected over 1074 observation hours, focus on 260 begging events (outside mother-offspring dyads) of which 37 % were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…This negative result could be simply explained by the fact that our macaques did not reciprocate juice reward delivery. Recent ethological report show the absence of short term contingencies between grooming and food tolerance in a different species of macaques (Molesti and Majolo, 2015) and in bonobos (Goldstone et al, 2016). This is somehow consistent with our results and underline the singularity of food sharing behaviors (Watson and Caldwell, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…This negative result could be simply explained by the fact that our macaques did not reciprocate juice reward delivery. Recent ethological report show the absence of short term contingencies between grooming and food tolerance in a different species of macaques (Molesti and Majolo, 2015) and in bonobos (Goldstone et al, 2016). This is somehow consistent with our results and underline the singularity of food sharing behaviors (Watson and Caldwell, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Food sharing may also provide a means to reinforce tolerant relationships among non‐kin. This is supported by evidence from LuiKotale (Goldstone, Sommer, Nurmi, Stephens, & Fruth, ) and Wamba (Yamamoto, ) that food begging is most frequently initiated by younger and more subordinate females and directed at older female food possessors, and may be used as a social tool to assess relationships. Goldstone et al, () found no relationship between the likelihood of receiving food and short‐term measures of grooming or GG‐rubbing between partners.…”
Section: Discussionmentioning
confidence: 70%
“…Specifically, hypotheses have been proposed to suggest that beggars are often not primarily interested in food but rather use the response of the possessor to ascertain information about their personality (the “information gathering” hypothesis; van Noordwijk and van Schaik 2009) or about the status of their relationship with them (the “assessing-relationships” hypothesis; Goldstone et al 2016). Related to this, some have suggested that food sharing can in fact be used not only to assess, but also to establish or reinforce social bonds (von Bayern et al 2007; Wittig et al 2014; Yamamoto 2015).…”
Section: Introductionmentioning
confidence: 99%